Myocardial Infarction in a 7-Year-Old Girl with Polyarteritis Nodosa - Bayazeed, Lina; Felimban, Alaa; Alsaiad, Abdulsalam; Alsufiani, Fahd; Alqanatish, Jubran (Case Reports in Rheumatology, 2022)
Polyarteritis nodosa (PAN) is a rare systemic vasculitis that affects small to medium-sized arteries. It could affect any organ including the heart. However coronary artery involvements are very rare. We describe a young girl who presented following a histopathological diagnosis of PAN with acute chest pain, high serum troponin, and progressive ischemic changes in the electrocardiogram (ECG). Induction of remission of her disease was done with six-moths Cyclophosphamide infusions and pulse corticosteroids. In addition to anticoagulation and dual antithrombotic therapy, the disease remission was maintained with mycophenolate mofetil which helps in the recovery of coronary disease. Our case illustrates the serious cardiac involvement of PAN in a child that responded to intensive management.